Nilai Ekonomi Lingkungan Pemanfaatan Limbah Cair Dan Limbah Tankos Hasil Pengolahan Industri Kelapa Sawit PT. Musirawas Citraharpindo - Afirus Febian; Danang Biyatmoko; Arief R. M. Akbar; Emmy Lilimantik (EnviroScienteae, 2020)
The development of plantations is currently accompanied by environmental issues arising from the waste from the palm oil industry. The utilization of waste to be of economic value is necessary to reduce negative impacts on the environment and create an environmentally friendly industry. Thus, it can reduce production costs, increase income, and not burden the environment. The purpose of this research is to analyze the environmental economic value of the utilization of liquid waste and tankos solid waste. This research method uses observation, interview, documentation, and economic valuation techniques. The results of the calculation of changes in the productivity of waste utilization as a reduction in the use of urea fertilizer, RP fertilizer, MOP fertilizer, and kieserite fertilizer provide an economic value of sludge liquid waste of IDR 46,644,326.72 and tankos solid waste of IDR 1,784,059,650.00. The results of the study conclude that the use of sludge liquid waste and tankos solid waste carried out by the company in 2017 with an applied area of 3,443.16 hectares was able to provide an environmental economic value of Rp. 1,830,703,967.72.